Analisis Pengalaman Belajar Menggunakan AI Dalam Dunia Pendidikan Pada Mahasiswa Baru PBSI FKIP UNSIKA - Amal, Bahar; Rakhmatusolikhah, Aulina; Peramita, Cicih; Jitmau, Mildret Sarina; Putri, Nur Anindya Dwi; Maharani, Syahrazade (LPPM STIKOM Tunas Bangsa, 2025)
The purpose of this study is to analyze the utilization of artificial intelligence (AI) to optimize the learning experience of first-year students at PBSI FKIP UNSIKA. As a rapidly advancing technology, AI can adapt to individual learning needs, enhance interactivity, and provide relevant learning recommendations. This research uses a questionnaire to assess the effectiveness of AI in facilitating the education of first-year students. The study examines the impact of AI on student engagement, academic performance, and overall learning effectiveness. The results are expected to offer insights into how AI can assist new students in accessing, understanding, and interacting with educational content. Additionally, this research aims to provide practical guidance for educators in integrating AI into higher education to enrich the learning experience and improve educational outcomes in the digital era